Evolutionary distinctiveness and conservation priority of the endangered Najas ancistrocarpa (Hydrocharitaceae). Issue 1 (2nd January 2018) - Ito, Yu; Enju, Chigaya; Li, Jie; Tanaka, Norio
Abstract : Phylogeny is vitally important to evaluate evolutionary distinctiveness and conservation priorities of species. Najas ancistrocarpa is one of the rarest and least known East Asian species of the c . 30–40 species of the aquatic plant genus Najas (Hydrocharitaceae). We used a recently discovered collection of this nationally and regionally endangered species in Japan and East Asia to assess whether N . ancistrocarpa is a distinct species or an untypical form of other Najas species and to evaluate its conservation priority in a phylogenetic context. The sample set of our previous study, exploring worldwide phylogeny of the genus was used with N. ancistrocarpa to delimit species boundaries in Najas and obtain conservation priority scores, calculated by multiplying evolutionary distinctiveness and global extinction risks converted from Red List categories. We performed molecular phylogenetic analyses of plastid (ptDNA) and nuclear (ITS) DNA datasets, STACEY species delimitation analysis using the multilocus dataset and a measurement of conservation priority with Tuatara. Najas ancistrocarpa was consistently placed in ptDNA and ITS trees. Species delimitation analysis objectively assessed that N . ancistrocarpa is phylogenetically distinct. Phylogenetic conservation prioritization ranked N . ancistrocarpa the second highest priority species of the genus Najas . Overall, in terms of biodiversity conservation, N . ancistrocarpa represents an important Najas species in Japan and probably the world.